An Optimized Drude's Equation For Polarization Measurement in the Visible Region and Concentrations Estimation - Yu Lei; Hongzhi Jia; Xun Xu; Shixin Jiang (IEEE Photonics Journal, 2018)
Drude's equation, a classical equation, can be used to express the properties of optic polarization. In the paper, an optimized two-term Drude's equation is introduced for expressing the specific rotation. The optical rotation angle for each wavelength is measured by a charge-coupled device. In order to verify the precision and versatility of the equation, we compare the obtained specific rotation with published analysis at a wavelength of 589.3 nm. Moreover, the two-term Drude's equation is translated into calculate the approximatively individual concentration of the molecules in aqueous solution. The calculation is based on the linear functional relation and fitting parameters of total rotation without knowing the ranges of concentrations and setting constraints. The viability and flexibility of this method demonstrate the potential applications in optics.